2015
DOI: 10.3892/ol.2015.3783
|View full text |Cite
|
Sign up to set email alerts
|

Changes in neutrophil/lymphocyte and platelet/lymphocyte ratios after chemotherapy correlate with chemotherapy response and prediction of prognosis in patients with unresectable gastric cancer

Abstract: The aim of the study was to investigate the application value of neutrophil to lymphocyte ratio (NLR) and the platelet to lymphocyte ratio (PLR) in the prediction of chemotherapy response and prognosis in patients with advanced gastric cancer. In total, 120 patients with unresectable gastric cancer were included and separated into two groups according to the median values of NLR or PLR (NLR low: <4.62 or NLR high: ≥4.62 and PLR low: <235 or PLR high: ≥235, respectively). Low baseline NLR level correlated with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
51
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 59 publications
(57 citation statements)
references
References 49 publications
6
51
0
Order By: Relevance
“…Treatment-induced changes in NLR also predicted survival. Both baseline NLR and changes upon initiation of treatment predicted treatment outcomes [38]. This finding is in accordance with Cho et al, who also reported significantly higher chemotherapeutic disease control rate in metastatic advanced gastric cancer patients having low NLR, defined as less or equal to 3.0 [50].…”
Section: Nlr and Survival: Prognostic Implicationssupporting
confidence: 89%
See 3 more Smart Citations
“…Treatment-induced changes in NLR also predicted survival. Both baseline NLR and changes upon initiation of treatment predicted treatment outcomes [38]. This finding is in accordance with Cho et al, who also reported significantly higher chemotherapeutic disease control rate in metastatic advanced gastric cancer patients having low NLR, defined as less or equal to 3.0 [50].…”
Section: Nlr and Survival: Prognostic Implicationssupporting
confidence: 89%
“…The biological differences were remarkable: the median survival associated with low vs. high NLR was 1209 vs. 587 days, respectively [16]. High NLR is associated with older age in some studies [9,20,44,47,54,55] while others report no association [22,38].…”
Section: Nlr and Survival: Prognostic Implicationsmentioning
confidence: 98%
See 2 more Smart Citations
“…Recent studies have suggested that a systemic inflammatory state is associated with the malignant biological behavior of the tumor (14,15). In particular, the neutrophil-lymphocyte ratio (NLR) has been evaluated as a predictor of prognosis in various types of solid tumor, including gastric, colorectal, pancreatic, breast and lung cancers (16)(17)(18)(19)). An elevated NLR has already been shown to be associated with poor prognosis in patients with HCC treated by liver transplantation, surgical resection, or TACE (20)(21)(22).…”
Section: Introductionmentioning
confidence: 99%